Perancangan Aplikasi Pembelajaran Statistika Dengan Menerapkan Metode Analysis Desain Develop Implement Evaluate (ADDIE) - Dermawa, Lusi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Development of learning methods that utilize technological developments with accessible computer media as a more effective way of learning. The use of these media makes it easier for participants to absorb the material and attracts the attention of students to learn actively. The learning method using animation media aims to facilitate students in teaching and make it easier for students to understand the material. With flash animation, students will get a real picture of abstract material. The purpose of this research and development is to produce animation learning media using macromedia flash 8. This study aims to help students understand and understand statistics learning material and this is a solution to several learning problems, namely explanation that is too fast, an atmosphere that is not conducive, time, learning media and student interests. Statistics is knowledge related to methods, techniques or ways to collect, process, analyze, interpret data to be presented completely in a form that is easy for users to implement. The learning method or model used to help students understand lessons quickly is a multimedia-based learning model called ADDIE (analysis-design-develop-implement-evaluation). Where the ADDIE method uses strategic learning methods by providing material, questions, examples, exercises, and quizzes. The aim is to make students understand the concept of the material better.